Effect of multiwalled carbon nanotube-grafted polymer brushes on the mechanical and swelling properties of polyacrylamide composite hydrogels. (24th February 2016) - Li, Zili; Tang, Miao; Dai, Jingwen; Wang, Taisheng; Bai, Ruke
Abstract: Diblock copolymers of poly(tert-butyl acrylate)-b-poly(azidomethyl styrene) were synthesized and used to modify multiwalled carbon nanotubes. After hydrolysis of the PtBA block, hydrophilic MWCNTs with poly(acrylic acid) brushes (MWCNT-PAA) were obtained and characterized. Then novel polyacrylamide composite hydrogels were prepared by in situ polymerization of acrylamide in presence of MWCNT-PAA. Our results show that the mechanical properties of the composite hydrogels are significantly improved with increasing the content of MWCNT-PAA. For the composite hydrogels, when the content of MWCNTs (weight ratio of MWCNT-PAA/AM) reached to 1.4 wt%, the tensile strength and the elongation were measured to be 82.7 kPa and 508% respectively, which are at least 3.9 and 3.1 times higher than those of the polyacrylamide hydrogel. Moreover, the swelling property of the hydrogel can be regulated through the content of MWCNT-PAA. Therefore, these hydrogels may have potential applications in biomedical fields without the limitations of water capacity and mechanical properties. Graphical abstract: Multiwalled carbon nanotube based polyacrylamide composite hydrogels with high strength were prepared by using multiwalled carbon nanotube-grafted polymer brushes and acrylamide through in situ polymerization. Highlights: Azide diblock copolymers of well-defined structure were synthesized through RAFT polymerization. Hydrophilic MWCNT with different length of PAA brushes were prepared. MWCNT based composite hydrogels with high strength and excellent stretchability were prepared by using MWCNT-PAA brushes. Mechanical properties and swelling property were highly dependent on the MWCNT-PAA brushes.